ChemInform Abstract: A New Approach for the Synthesis of Highly Substituted Aromatic Rings: The Alkyne‐Mediated Approach. Issue 31 (14th July 2016) - Parsons, Philip J.; Jones, Daniel R.; Padgham, Alex C.; Allen, Lewis A. T.; Penkett, Clive S.; Green, Robert A.; White, Andrew J. P.
Abstract: Pentasubstituted aromatic rings, useful templates for drug design, are prepared by thermolysis of suitably substituted alkynes under microwave conditions.